2015
DOI: 10.1007/s12010-015-1882-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light Stress and Other Culture Conditions on Photoinhibition and Growth of Dunaliella tertiolecta

Abstract: This work aimed to examine the effects of high light stress as well as other culture conditions including HCO3 − concentration, temperature, salinity, and pre-acclimation on photoinhibition and growth of halotolerant alga Dunaliella tertiolecta. Significant photoinhibition of D. tertiolecta was observed during a short period of exposure (6 hours) to high intensity of lights (1000, 1500, and 2000 μmol photons m-2 s-1); however, after 2 days of continuous light exposure, the alga adapted to high light stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
1
9
0
2
Order By: Relevance
“…tertiolecta was observed during a short period of exposure to high intensities of light, but after continuous light exposure, the algal cells adapted to the high light stress and reached similar growth rates as in low light exposure; it indicates that a preacclimation condition for D. tertiolecta can be used to reduce the inhibitory effect of high light intensity on the growth of algal cells …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…tertiolecta was observed during a short period of exposure to high intensities of light, but after continuous light exposure, the algal cells adapted to the high light stress and reached similar growth rates as in low light exposure; it indicates that a preacclimation condition for D. tertiolecta can be used to reduce the inhibitory effect of high light intensity on the growth of algal cells …”
Section: Resultsmentioning
confidence: 92%
“…39 A previous study suggested that significant photoinhibition of D. tertiolecta was observed during a short period of exposure to high intensities of light, but after continuous light exposure, the algal cells adapted to the high light stress and reached similar growth rates as in low light exposure; it indicates that a preacclimation condition for D. tertiolecta can be used to reduce the inhibitory effect of high light intensity on the growth of algal cells. 40 The changes of the pigment content in D. tertiolecta treated with various concentrations of piperonyl butoxide under the light intensities of 6000, 8000, and 10,000 Lux were studied. Figure 3C shows the change in the content of carotenoids in D. tertiolecta treated with each concentration of piperonyl butoxide for 4 days with the light intensities of 6000, 8000, and 10,000 Lux.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ở D. tertiolecta sự quang ức chế thực sự xảy ra trong thời gian ngắn (6 giờ đầu) sau ức chế ánh sáng cao (1000, 1500 và 2000 µmol/m 2 /s), tuy nhiên sau 2 ngày ức chế ánh sáng cao liên tục D. tertiolecta đáp ứng được với điều kiện ánh sáng cao này và tốc độ tăng trưởng đạt được như điều kiện ánh sáng thấp. Điều này cho thấy D. tertiolecta có thể đáp ứng với phổ rộng ánh sáng cao từ 50-2000 μmol photons/m 2 /s [14]. Theo Yilancioglu và cộng sự, khi xử lí H2O2 ngoại sinh nồng độ từ 200µM-4mM cho thấy sự sống sót của tế bào D. salina giảm dần, tuy nhiên nồng độ ROS và lipid tăng cao [5].…”
Section: Sự Tăng Trưởng Của Dunaliella Salinaunclassified
“…Ngoài ra, sau 2 ngày nuôi cấy, tỉ lệ Fv/Fm không có khác biệt giữa các điều kiện độ muối khác nhau khi nuôi trong điều kiện nuôi ánh sáng thấp; tuy nhiên tỉ lệ này có sự khác biệt giữa các độ muối khi nuôi cấy dưới điều kiện ánh sáng cao. Sự giảm tỉ lệ Fv/Fm cho thấy tế bào D. tertiolecta bị quang ức chế trong điều kiện ánh sáng cao [14].…”
Section: Hàm Lượng Diệp Lục Tốunclassified
“…For light stress adaptation of C. vulgaris , a small culture sample of 2 ml was subjected to intense light of 1,950 μ mol∗s −1 ∗m −2 photons of photosynthetically active radiation for 1 day prior to the measurement, with the culture returned to the stress light between the recording of individual spectra to maintain the stressed state. The intensity for stress light was selected according to values given in Seepratoomrosh et al() Due to the small total sample size, the light stress experiment was repeated twice. According to Koch et al, the violaxanthin cycle of the green alga Dunaliella salina reacts to light stress within 3.2 min.…”
Section: Experimental Aspectsmentioning
confidence: 99%